A Study of Communication Skills among Post Graduate Students in Kolhapur University India - Supriyati Patil; Nagina Mali (Lingkar Studi Komunikasi (LISKI), 2023)
This study was done to find out the performance of student lecturers in Communication Skills at the Department of Education, Shivaji University, Kolhapur, Maharashtra, India. The research also had an aim of bringing suggestions and recommendations on how to improve Communication Skills of Students and Lecturers. In order to do this, the researcher used Questionnaire with multiple choice and open-ended questions to collect data in order to answer the questions that this research seeks to answer. The study targeted were student and lecturers of the Department of Education, Shivaji University, Kolhapur and purposive sampling technique used to select thirty students and lecturers. Collected data is analyzed by using percentage data analysis tool. Keywords: Communication Skills, Graduate Students, Lecturers, India School.